Onikomikosis yang Disebabkan oleh Kodamaea ohmeri pada Seorang Pasien dengan Virus Imunodefisiensi Manusia (HIV) – Laporan Kasus: Laporan Kasus - Nadliroh, Siti; Wahid, Mardiastuti; Sjatha, Fithriyah; Haliman, Cliff Clarence; Widaty, Sandra; Mutiara, Rizka; Pratama, Aditya Indra; Asri, Rizkia Chairani; Adawiyah, Robiatul; Kusumaningrum, Ardiana (PT Kalbe Farma Tbk., 2026)
Introduction: Onychomycosis is a fungal nail infection usually caused by dermatophytes. Kodamaea ohmeri is a rare fungus that has been reported as a pathogen capable of causing onychomycosis and systemic infections. This yeast-like fungus is often misidentified as Candida sp. A complete identification is required for accurate results. Case: A 40-year-old male with HIV presented with yellow and brittle fingernails for 2 months. KOH examination of nail scrapings was performed, followed by fungal culture. The isolate was identified in parallel using the Integral System Yeast Plus, Vitek-2, MALDI-TOF (Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry), and sequencing, and the result was Kodamaea ohmeri. The patient received oral itraconazole and topical ketoconazole. Discussion: Onychomycosis in HIV patients is caused by low immunity, high viral load, and low CD4 values. In this case, K. ohmeri was successfully identified using Vitek-2, MALDI-TOF, and ITS (Internal Transcribed Spacer) area sequencing, while the Integral System Yeast Plus misidentified the isolate as Candida tropicalis. There was clinical improvement in the nail after treatment. Conclusion: Onychomycosis in HIV patients can be caused by Kodamaea ohmeri. Identification can be done with Vitek-2 and MALDI-TOF.